Microscopy and Chemical Composition of Healthy and Resinous Wood from the Agarwood-Producing Species, Aqualaria Beccariana - Hamdan, Mohammad M.S.; Huq, A.K.M. Moyeenul; Che M.A.B., Che Mohd; Siti H.N.B., Shaarani; Lee, Shiou Y.; Hanafi, Anuwar; Saiful N., Tajuddin (Biointerface Research, 2024)
Aquilaria beccariana is a vulnerable Malaysian agarwood-producing species due to illegal harvesting and indiscriminate deforestation. Despite its current conservation status, the chemical profiling of this valuable species is seemingly non-existent. The current study aimed to evaluate the morphological characteristics of A. beccariana wood and identify the volatile chemical compounds of its wood and essential oil. The field emission scanning electron microscope (FESEM) was used to study the wood morphology, while gas chromatography with flame ionization detection and gas chromatography coupled with mass spectrometry was used. The FESEM analysis revealed that vessel pits were distinct in the healthy wood samples but hardly visible in the resinous wood sample. The monoterpene, sesquiterpenes, and sesquiterpenoid were detected, whereby 35 constituents were from the resinous wood sample, which consisted of 15.29% sesquiterpenes and 50.68% sesquiterpenoid. The major compounds were kessane, α-longipinene, α-curcumene, eudesmol, and epi-α-bisabolol. Approximately 32 compounds were identified in the essential oil sample, comprising 36.69% of sesquiterpenes and 49.58% of sesquiterpenoids. The principal compounds were 7-epi-γ-eudesmol, γcadinene, allo-aromadendrene, kessane, and nor-ketoagarofuran. This study provides valuable information on the volatile chemical compound profiles of A. beccariana; thus, it would further contribute to the search for potential chemical markers for species detection and agarwood classification efforts.